Protection of liver sinusoidal endothelial cells using different preservation solutions - Julia H E Houtzager; Anne-Marieke van Stalborch; Charlotte Hofstee; Thomas M van Gulik; Jaap D van Buul (Vascular Biology)
Donor liver preservation methods and solutions have evolved over the last years. Liver sinusoidal endothelial cell (LSEC) barrier function and integrity during preservation are crucial for outcomes of liver transplantation. Therefore, the present study aimed to determine optimal preservation of LSEC barrier function and integrity using different preservation solutions. Human umbilical vein endothelial cells (HUVECs) and LSECs were incubated in either University of Wisconsin machine perfusion solution (UW-MPS), histidine-tryptophan-ketoglutarate, or endothelial cell growth medium 2 (EGM2) (as a gold standard for cell culturing). Endothelial integrity was assessed by measurement of cellular morphology and expression of membrane proteins: PECAM-1, ICAM-1 and Fc-gamma receptor CD32b (FcΥRCD32b). Endothelial barrier function was measured by electric cell-substrate impedance sensing. Cellular response to inflammatory stimuli with tumor necrosis factor-alpha (TNF-α) was tested by studying trans-endothelial migration (TEM) under flow conditions. Differences in these parameters were analyzed between the different preservation solutions. PECAM-1 expression was high for all preservation solutions in HUVECs and LSECs. ICAM-1 expression was increased in both LSECs and HUVECs in all preservation solutions plus TNF-α. UW reduced PECAM-1 expression, whereas EGM2 medium promoted barrier function in LSECs and HUVECs, and monolayer recovery after wounding was best achieved in cells incubated in EGM2. LSECs and HUVECs incubated with EGM2 plus TNF-α both supported neutrophil adhesion and TEM, but much less to none when incubated in UW plus TNF-α. Overall, EGM2 showed the best results in preserving endothelial barrier function for both HUVECs and LSECs.